Monitoring of Heparin Therapy with the Activated Partial Thromboplastin Time and Chromogenic Substrate Assays - Fey, Martin F; Lang, Mathis; Furlan, Miha; Beck, Eugen A (Thrombosis and Haemostasis, 1987)
Heparin therapy was monitored with the activated partial thromboplastin time (APTT) and with chromogenic substrate assays (factor Xa and factor Ha inhibition) in 100 plasma samples from 47 patients. Heparin concentrations were classified as being below, within or above a defined therapeutic range (TR; 0.2-0.55 units heparin/ml). In a first group of patients (A), all three assays allocated the plasma heparin levels to the same concentration interval with respect to the TR. The most frequent diagnoses in group A were uncomplicated arterial or venous thromboembolism, myocardial infarction with limited tissue necrosis, cardiac surgery without major complications and successfully treated infectious disease. In a second group of patients (B), the results of APTT suggested higher heparin concentrations with respect to the TR than the chromogenic assays. Predominant diagnoses were severe infectious diseases, severe liver disorders, extensive myocardial infarction and postoperative complications after cardiac surgery. The discrepancy between heparin concentrations determined by either APTT or the chromogenic substrate assays is most likely due to a non-heparin related prolongation of APTT caused by the underlying disease.
Keywords: Heparin therapy; Heparin monitoring; Chromogenic substrate assays; Activated partial thromboplastin time; Acquired coagulation disorders